2013
DOI: 10.1645/13-176.1
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Levels in Serum and Adenosine Deaminase Activity in Blood Cells of Dogs Infected byRangelia vitalii

Abstract: Ecto-adenosinedeaminase (E-ADA) plays an important role in the production and differentiation of blood cells as well as in the control of extracellular adenosine levels. Infectious diseases can influence the synthesis of new cells or cause cell destruction, as occurs in canine rangeliosis, which results in anemia, thrombocytopenia, leukocytosis, and/or leukopenia. Thus, this study aimed to evaluate E-ADA activity in sera, erythrocytes, lymphocytes, and adenosine levels in sera samples of dogs infected by Range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…Therefore, the stability of COR in rat matrices followed the order: whole blood ≈ hematocyte > plasma. This finding could be because the activities of ADA in the rat's whole blood, plasma, and hematocyte of rat were different (whole blood ≈ hematocyte > plasma), which is consistent with the results reported in the literature [25]. To inhibit the degradation of COR in collected rat blood samples, ADA inhibitor EHNA was initially selected as the stabilizer of COR.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the stability of COR in rat matrices followed the order: whole blood ≈ hematocyte > plasma. This finding could be because the activities of ADA in the rat's whole blood, plasma, and hematocyte of rat were different (whole blood ≈ hematocyte > plasma), which is consistent with the results reported in the literature [25]. To inhibit the degradation of COR in collected rat blood samples, ADA inhibitor EHNA was initially selected as the stabilizer of COR.…”
Section: Discussionsupporting
confidence: 85%
“…Our results are concordant with the findings reported by other researchers relating to experimental infection of dogs with E. canis (Da Silva et al 2013a) and Rangelia vitalii (Da Silva et al 2013b). Considering the immune response of diseases, it is generally recognized that cell-mediated immunity is important in protection against intracellular parasites.…”
supporting
confidence: 93%
“…Recently, a study conducted by Da Silva et al. () demonstrated that upregulation of ADA activity contributed to intense inflammatory damage in dogs naturally infected with the protozoan Rangelia vitalii, which contributes directly to disease pathophysiology. In particular, Domínguez Artiga, Holanda Peña, Velasco, Orozco Abril, and Teja Barbero () demonstrated that upregulation of ADA activity may have contributed to disease pathogenesis during bacterial meningitis caused by Streptococcus pneumoniae , in accordance to results observed in the present study.…”
Section: Discussionmentioning
confidence: 99%